In Vitro Sensitivity Profiling of Neuroblastoma Cells Against A Comprehensive Small Molecule Kinase Inhibitor Library to Identify Agents for Future Therapeutic Studies - Singh, Anjali; Meier-Stephenson, Vanessa; Jayanthan, Aarthi; Narendran, Aru (Current Cancer Drug Targets, 2017)
Background: Neuroblastoma (NB) constitutes about 8% of all childhood tumors, yet accounts for more than 15% of deaths, with an unacceptable overall survival rate. These rates are despite the current multimodal therapeutic approaches involving surgery, radiation, chemotherapy and myeloablation with hematopoietic stem cell rescue. Hence, efforts have intensified to identify new targets and novel therapeutic approaches to improve cure rates in these children. Numerous new agents for adult malignancies are developed and evaluated for cancer each year, providing an invaluable resource, with the added advantage of available pharmacologic and toxicity data for consideration. Methods: To identify potential therapeutic targets, we screened a small molecule library of 151 small kinase inhibitors against NB cell lines. Based on our initial screening data, we further examined the potential of Bcr-Abl targeting small molecule inhibitors to affect the growth and survival of NB cells. Results: There is diverse activity among the currently available Bcr-Abl inhibitors, possibly reflecting the molecular heterogeneity and off-target activity in each combination. In depth analyses of ponatinib, an oral multi-target kinase inhibitor and effective agent in the treatment of refractory Philadelphia chromosome (Ph) positive leukemia, show growth inhibition at sub-micromolar concentrations. In addition, we also identified the potential of this agent to interfere with insulin-like growth factor-1 receptor (IGF-1R) signaling pathways and Src activity, inhibit cell migration and induce apoptosis. Conclusion: Our findings provide initial data on ponatinib's potential to target key growth regulatory pathways and provide the rationale for further studies and evaluation in future early phase clinical trials for the treatment of refractory NB.
Keywords: Src